Pengaruh Audit Tenure dan Kompleksitas Operasi Terhadap Audit Delay Perusahaan Pertambangan di BEI Tahun 2013-2016 - Pratiwi, Cokorda Istri Eka; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
Delay in publish report finance audits can be a serious problem for company that goes public in Indonesia Stock Exchange. Therefore, it is necessary to conduct a research studying about determination of factors that might affect audit delay. The purpose of this study is to obtain empirical evidence about the effect of tenure audit and complexity operation on audit delay. This research was conducted at a mining company listed on Indonesia Stock Exchange with period of research in year 2013-2016. The method of determining the sample in this study using purposive sampling method with the number of samples 104 samples for 2013-2016 periods. Data analysis technique applied in this research is multiple linear regression. Results research this showed that audit tenure has no effect on audit delay, while complexity operation has a positive effect on audit delay. Keywords: audit delay, tenure audit, complexity operation